A paleogeodetic record of variable interseismic rates and megathrust coupling at Simeulue Island, Sumatra - Tsang, Louisa Lok Hang (2016)
An ∼1100 year long paleogeodetic record of land-height change along the Simeulue section of the Sumatran subduction zone reveals significant variations in vertical motion rates. From an ∼267 year long record, we develop models to explain rate variations in the decades before the 1861, 2004, and 2005 great earthquakes. The record shows that rates accelerated by a factor of 4 to 10 in the decades before the 1861 earthquake; one plausible explanation is a significant increase in the depth of interseismic coupling on the Sunda megathrust under Simeulue. Despite similarity of the 1861 and 2005 coseismic rupture patterns, the pattern of coupling during the decades before the two earthquakes may have been different. Most GPS observations of interseismic deformation at subduction zones span only a decade or two; our results highlight the need to treat GPS-derived coupling maps as only a snapshot of fault conditions that are temporally variable.